A Study on the perceived drivers of urban regeneration projects - LEE, Sookyoung (KDI School, 2023)
Urban regeneration has taken a significant part of urban policy for several decades. The conceptual framework was founded on the awareness of 'the limit to growth' and provided the basis for sustainable - economically efficient, socially inclusive, environmentally eco-friendly, technologically high-end, and above all, nonharmful to the interest of future generations - urban development. It is the ultimate ideal vision conceptually, which can address not only the urban issues but also most of the present global concerns. However, these ideal and comprehensive features inherently expose urban regeneration policy to controversies, and carry a significant potential for partial achievement and substantial room for failure in certain aspects. By the same token, the urban regeneration policy is currently being questioned for its feasibility and at stake amid the challenges of policy keynote change in Korea. This study was started from the question ‘why this ideal policy fails to attain decent social consensus, and what for it is questioned the most’. A considerable body of scholarship has dealt with this topic in recent years, but little research has done in empirical terms. This capstone aimed to pragmatically diagnose the policy efficacy on-site through the perspective of policy implementors. To achieve this, the study conducted a survey targeting individuals responsible for urban regeneration projects in their respective regions. As a result, the study found that overall sentiments regarding accomplishment and problematic issues align with those of public appraisals and critiques. Perceptions of policy effectiveness, including the appropriateness of policy goals and indicators, generally hover around the median. Evaluation ratings for most inquiries on the degree of achievement are much dispersed without certain consistency. In contrast, the responses regarding external factors such as ruling regime influence and side-effects of the policy clearly exhibit clear patterns. The results suggest that urban regeneration policy needs to be more realistic and a consistent customization process to realize the policy goals.
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Sustainable urban development--Korea (South); Urban renewal--Korea (South)